Otolaryngology in the Time of Corona: Assessing Operative Impact and Risk During the COVID‐19 Crisis. (2nd June 2020) - Kuhar, Hannah N.; Heilingoetter, Ashley; Bergman, Maxwell; Worobetz, Noah; Chiang, Tendy; Matrka, Laura
Abstract : Objective: Limited research exists on the coronavirus disease 2019 (COVID‐19) pandemic pertaining to otolaryngology–head and neck surgery (OHNS). The present study seeks to understand the response of OHNS workflows in the context of policy changes and to contribute to developing preparatory guidelines for perioperative management in OHNS. Study Design: Retrospective cohort study. Setting: Pediatric and general adult academic medical centers and a Comprehensive Cancer Center (CCC). Subjects and Methods: OHNS cases from March 18 to April 8, 2020—the 3 weeks immediately following the Ohio state‐mandated suspension of all elective surgery on March 18, 2020—were compared with a 2019 control data set. Results: During this time, OHNS at the general adult and pediatric medical centers and CCC experienced 87.8%, 77.1%, and 32% decreases in surgical procedures as compared with 2019, respectively. Aerosol‐generating procedures accounted for 86.8% of general adult cases, 92.4% of pediatric cases, and 62.0% of CCC cases. Preoperative COVID‐19 testing occurred in 7.1% of general adult, 9% of pediatric, and 6.9% of CCC cases. The majority of procedures were tiers 3a and 3b per the Centers for Medicare & Medicaid Services. Aerosol‐protective personal protective equipment (PPE) was worn in 28.6% of general adult, 90% of pediatric, and 15.5% of CCC cases. Conclusion: For OHNS, the majority of essential surgical cases remained high‐risk aerosol‐generating procedures. Preoperative COVID‐19 testing and intraoperative PPE usage were initially inconsistent; systemwide guidelines were developed rapidly but lagged behind recommendations of the OHNS department and its academy. OHNS best practice standards are needed for preoperative COVID‐19 status screening and PPE usage as we begin national reopening.